1998
DOI: 10.1029/98ja01104
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency electromagnetic turbulence observed near the substorm onset site

Abstract: On the basis of wave and plasma observations of the Geotail satellite, the instability mode of low‐frequency (1–10 Hz) electromagnetic turbulence observed at the neutral sheet during substorms has been examined. Quantitative estimation has also been made for the anomalous heating and resistivity resulting from the electromagnetic turbulence. Four possible candidates of substorm onset sites, characterized by the near‐Earth neutral line, are found in the data sets obtained at substorm onset times. In these event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
94
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 54 publications
(28 reference statements)
8
94
0
Order By: Relevance
“…Unfortunately, theory predicts the fastest growing modes with a wavelength on the electron gyroscale k y e 1 are localized on the edge of the layer [5], while enhanced fluctuations are required in the central region to produce significant anomalous resistivity. This conclusion is supported by observations at the magnetopause [9], in the magnetotail [10], and by laboratory experiments [11].…”
supporting
confidence: 75%
“…Unfortunately, theory predicts the fastest growing modes with a wavelength on the electron gyroscale k y e 1 are localized on the edge of the layer [5], while enhanced fluctuations are required in the central region to produce significant anomalous resistivity. This conclusion is supported by observations at the magnetopause [9], in the magnetotail [10], and by laboratory experiments [11].…”
supporting
confidence: 75%
“…Three-dimensional particle simulations [8] and Hall MHD simulations [9] have actually shown that the LHDI does develop in the current sheet, but have conflicting views on the role of the turbulence: the former shows that LHDI can assist in driving reconnection (through profile modification or by assisting in electric field penetration), while the latter shows that LHDI can actually slow reconnection relative to laminar two-dimensional simulations. There is observational evidence for the existence of the LHDI in the magnetotail current sheet [10], where it may trigger current disruptions [11]. Earlier laboratory studies of fluctuations have revealed evidence for unstable ion acoustic and whistler waves in current sheets [12], but the ion gyroradius in these experiments was larger than the apparatus size and excitation of instabilities such as the LHDI might not have been possible.…”
mentioning
confidence: 87%
“…4 Since it is a relatively short wavelength and high frequency instability, the LHDI has been considered for some years a source of anomalous resistivity, 5,6 and it is often invoked to explain the discrepancy between the rapid observed rate of reconnection and the slow, theoretically predicted Sweet-Parker rate based on classical resistivity. Indeed the LHDI has been observed during magnetic reconnection in the magnetotail, 7 in the magnetopause, 8 and in laboratory experiments. 9 However, two problems make the explanation of anomalous resistivity based on LHDI difficult to accept.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, two problems make the explanation of anomalous resistivity based on LHDI difficult to accept. First, both simulations 10 and observations 7,9 show that the saturation level of the LHDI is determined primarily by the electron dynamics, and it is far too low to justify the anomalous resistivity that is required to obtain realistic reconnection rates within the Sweet-Parker model. Second, the LHDI is mostly stabilized at high plasma ␤ and thus it grows primarily on the flanks of the current sheet, 11 unless the current layer is very thin.…”
Section: Introductionmentioning
confidence: 99%